A locus for asphyxiating thoracic dystrophy, ATD, maps to chromosome 15q13. Issue 6 (1st June 2003) - Morgan, N V; Bacchelli, C; Gissen, P; Morton, J; Ferrero, G B; Silengo, M; Labrune, P; Casteels, I; Hall, C; Cox, P; Kelly, D A; Trembath, R C; et al.
Abstract : Asphyxiating thoracic dystrophy (ATD), or Jeune syndrome, is a multisystem autosomal recessive disorder associated with a characteristic skeletal dysplasia and variable renal, hepatic, pancreatic, and retinal abnormalities. We have performed a genome wide linkage search using autozygosity mapping in a cohort of four consanguineous families with ATD, three of which originate from Pakistan, and one from southern Italy. In these families, as well as in a fifth consanguineous family from France, we localised a novel ATD locus ( ATD ) to chromosome 15q13, with a maximum cumulative two point lod score at D15S1031 (Zmax=3.77 at ϑ=0.00). Five consanguineous families shared a 1.2 cM region of homozygosity between D15S165 and D15S1010. Investigation of a further four European kindreds, with no known parental consanguinity, showed evidence of marker homozygosity across a similar interval. Families with both mild and severe forms of ATD mapped to 15q13, but mutation analysis of two candidate genes, GREMLIN and FORMIN, did not show pathogenic mutations.